Introducing genre and English for specific purposes - Hyon, Sunny (Routledge, 2018)
Introducing Genre and English for Specific Purposes provides an overview of how genre has been conceptualized and applied in ESP, as well as the features that distinguish ESP genre research and teaching from those of other genre schools. The macro and micro aspects of ESP genre-based pedagogy are also analysed and include: different possibilities for planning and designing an ESP genre-based course; the concrete, micro aspects of materials creation; and how genres can be learned through play.